2006
DOI: 10.3133/sir20055235
|View full text |Cite
|
Sign up to set email alerts
|

A cyclostratigraphic and borehole-geophysical approach to development of a three-dimensional conceptual hydrogeologic model of the karstic Biscayne aquifer, southeastern Florida

Abstract: 10-12. Diagrams showing: 10. Idealized fifth-order cycles for the Fort Thompson Formation and Miami Limestone showing relations between lithofacies, depositional environments, porosity (pore classes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 23 publications
1
69
0
Order By: Relevance
“…2), the Q5e unit is characterized by a Schizoporella-bearing peloid packstone and grainstone lithofacies (Cunningham et al, 2006b), which is dominated by an Ophiomorpha ichnofabric. Based on mapping by Cunningham et al (2006b), the peloid packstone and grainstone lithofacies resembles the bryozoan facies described and interpreted by Hoffmeister et al (1967) to represent an open-marine shelf lagoon (Fig. 2); Perkins (1977) and Evans (1984) interpreted the facies as an open-marine platform.…”
Section: Geologic Settingmentioning
confidence: 99%
“…2), the Q5e unit is characterized by a Schizoporella-bearing peloid packstone and grainstone lithofacies (Cunningham et al, 2006b), which is dominated by an Ophiomorpha ichnofabric. Based on mapping by Cunningham et al (2006b), the peloid packstone and grainstone lithofacies resembles the bryozoan facies described and interpreted by Hoffmeister et al (1967) to represent an open-marine shelf lagoon (Fig. 2); Perkins (1977) and Evans (1984) interpreted the facies as an open-marine platform.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Moreover, geologic core analyses and high‐resolution photography of boreholes at the test site indicated that this uniquely higher conductivity most probably is associated to a discrete horizontal flow zone between 12.2 and 13.1 meters below land surface (bls) (Renken et al. , 2005; Cunningham et al. , 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Even though the newly reported transmissivity values are only 2‐4 times higher than the earlier reported values by Fish and Stewart (1991), the dominance of the transmissivity value is attributed to the discrete horizontal flow zone between 12.2 and 13.1 meters bls. Core analyses and high‐resolution photography at other locations indicated that this “conduit‐like” flow zone might extend throughout the capture area of the Northwest well field (Cunningham et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Biscayne Aquifer rock-porosity classifications were also obtained from Cunningham et al (2006). The literature describes a large range in hydrologic properties throughout the Biscayne Aquifer karst that is a result in nested pore networks sometimes referred to as a triple porosity system.…”
Section: Biscayne Aquifermentioning
confidence: 99%